Preparation method and application of porous MOF
By using triblock copolymer and metal ion diffusion optimization model in the synthesis process of MOF materials and combining surface functionalization technology, the problems of uneven distribution of metal ions and insufficient surface structure stability in porous MOF materials are solved, and the electrochemiluminescence performance and reliability of the material are significantly improved.
Patent Information
- Application Number
- CN202510208984.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing porous MOF materials face problems of uneven metal ion distribution and insufficient surface structure stability in electrochemiluminescence sensors, resulting in limited adsorption performance and reaction efficiency.
The triblock copolymer PluronicF-127 self-assembles, adjusts the concentration of acetic acid and sodium chloride, and controls the stirring rate to create a suitable environment to form a specific pore structure. At the same time, metal ion diffusion optimization model is adopted to adjust the temperature and reaction time to ensure uniform distribution of metal ions, and the introduction of amino and carboxy groups through surface functionalization, enhancing the stability and electrochemiluminescence activity of the material.
The uniform distribution of metal ions and the surface structure stability of MOF materials are achieved, and the reliability and electrochemiluminescence properties of the materials are improved in electrochemical reactions.
Smart Images

Figure CN119708531A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal organic framework preparation, and more specifically, to a preparation method and application of a porous MOF. Background Art
[0002] In the current electrochemiluminescence (ECL) sensor applications, metal organic framework (MOF) materials have become a hot topic of research due to their unique high surface area, good structural adjustability, and ability to embed different functional groups. Especially in the field of sensors, MOF materials have received extensive attention due to their high electrochemiluminescence efficiency and good reaction activity. However, existing porous MOF materials face problems of uneven metal ion distribution and insufficient surface structural stability in practical applications, both of which limit their adsorption performance and reaction efficiency in electrochemiluminescence sensors.
[0003] First, the metal ion distribution of existing MOF materials is usually relatively uneven. The uniform distribution of metal ions is crucial to the physical and chemical properties of MOF materials, especially in electrochemiluminescent sensors, where the uniform distribution of metal ions directly affects their adsorption and reaction capabilities to different molecules (such as substances to be measured, electrons or ions). In porous MOF materials, the distribution of metal ions is often affected by the synthesis conditions and reaction process. However, due to the limitations of reaction conditions and the selection of metal salts, existing MOF materials usually cannot form uniformly distributed metal ions. Although some MOF materials have a high specific surface area, the uneven distribution of metal ions makes it impossible to fully exert their adsorption and reaction performance. This uneven distribution of metal ions not only affects its adsorption performance, but also limits its efficiency in electrochemiluminescence reactions. Especially when rapid transfer of electrons and ions is required, MOF materials with uneven distribution of metal ions often cannot provide sufficient reaction sites and electron conduction capabilities, resulting in unstable electrochemical reaction efficiency and luminescence performance.
[0004] Secondly, the surface structure stability of existing MOF materials is poor, which is particularly evident during high temperature or long-term use. The structure of MOF materials is composed of metal ions and organic ligands connected by coordination bonds. Although this structure can maintain a high degree of stability in the early stage of synthesis, during the electrochemical reaction, especially under high voltage or long-term reaction conditions, the coordination bonds may be destroyed, resulting in changes in the surface of the MOF material, thereby affecting its electrochemiluminescence performance. Some MOF materials may undergo ligand desorption, metal center redox reactions or other structural changes during electrochemical reactions, which will cause the luminescence of the material to decay or even lose its original performance. Especially in the practical application of sensors, the stability of the material is a crucial factor. If the surface of the MOF material changes during long-term use, the sensitivity and repeatability of the sensor will decrease significantly, which will affect the accuracy and reliability of the detection results.
[0005] The existing public patent (a preparation method and application of electrochemiluminescent fluorescent hierarchical porous MOF, CN118185051A) discloses a preparation method and application of electrochemiluminescent fluorescent hierarchical porous MOF, which uses zirconyl nitrate as a metal source, combined with 2-aminoterephthalic acid and terpyridine ruthenium as co-ligands, and uses triblock copolymer templates and Hofmeister effect to synthesize porous MOF under mild conditions in aqueous phase, and achieves highly sensitive detection of micro RNA in tumor cells through the strong capture ability of zirconium-oxygen nodes for phosphate. However, although this method optimizes the pore structure through the template method, it does not systematically regulate the uniform distribution of metal ions, and the surface stability mainly depends on the chemical properties of the ligand itself, which may lead to uneven distribution of metal ions or ligand desorption in long-term applications.
[0006] In summary, although MOF materials have great potential for application in electrochemiluminescence sensors, defects in existing technologies still exist. The uneven distribution of metal ions limits the adsorption performance and reaction efficiency of MOF materials in sensors, and the poor stability of the surface structure reduces its reliability in long-term use. Therefore, a new preparation method for MOF materials is urgently needed, which can simultaneously solve the problems of uneven distribution of metal ions and surface structure stability, so as to meet the requirements of electrochemiluminescence sensors for high sensitivity and high stability. Summary of the invention
[0007] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a method for preparing and applying a porous MOF, which is to create a suitable environment for the synthesis of MOF by means of self-assembly of the triblock copolymer Pluronic F-127, adjusting the concentrations of acetic acid and sodium chloride, controlling the stirring rate, etc., which is conducive to the formation of a specific pore structure; through the metal ion diffusion optimization model, the temperature and reaction time are adjusted to ensure the uniform distribution of metal ions; amino and carboxyl groups are introduced to enhance the surface stability and electrochemiluminescence activity of MOF, so as to solve the problems raised in the above-mentioned background technology.
[0008] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a porous MOF comprises the following steps: Step S1, dissolving the triblock copolymer Pluronic F-127 in ultrapure water, adding acetic acid and sodium chloride, and stirring to form a solution.
[0009] Step S2, adding zirconium oxynitrate into the solution, and adjusting the temperature and reaction time through the metal ion diffusion optimization model to ensure uniform distribution of metal ions.
[0010] Step S3, introducing organic ligands to adjust the pore size distribution of MOF.
[0011] Step S4, performing surface functionalization on the synthesized MOF material to introduce amino groups and carboxyl groups.
[0012] Step S5, washing and filtering the synthesized MOF material to remove impurities and residues, and then drying the MOF material under vacuum conditions to remove moisture and organic solvents.
[0013] The steps of the metal ion diffusion optimization model are as follows: Step Q1, the metal ion diffusion equation after adding zirconium oxynitrate into the solution is: ,in, is the concentration of metal ions in zirconium oxynitrate, is the diffusion coefficient, is the Laplace operator; Step Q2, use the Arrhenius equation to describe the effect of temperature on the diffusion coefficient Impact: ,in, is the pre-exponential factor, is the activation energy, is the gas constant, is temperature; Step Q3, the solution concentration distribution during the reaction follows: ,in, is the initial metal ion concentration, is the spatial position of the metal ion in the solution, is the reaction time, is the error function; Step Q4, establish the objective function, combine temperature and time, and optimize the uniformity of metal ions: ,in, is the length of the solution container, is the average concentration of metal ions, by adjusting the temperature and reaction time , to achieve uniform distribution of metal ions.
[0014] As a further solution of the present invention, in the metal ion diffusion optimization model, satisfy , in order to make the concentration of metal ions uniformly distributed, minimize the objective function , the calculation formula is: , locally linearize the error function and calculate the gradient of the objective function: , , iteratively update the temperature by gradient descent method and reaction time , the update formula is as follows: , ,in, is the learning rate, which controls the step size of each update.
[0015] As a further embodiment of the present invention, in step S1, the triblock copolymer Pluronic F-127 is a block copolymer composed of polyether and polypropylene glycol (PPO), and its molecular structure characteristics enable it to spontaneously form a micellar structure in solution. The molecular self-assembly behavior of the triblock copolymer Pluronic F-127 in solution helps to form a microstructure, which can not only adjust the viscosity and interfacial tension of the solution, but also affect the formation of the MOF pore structure during the synthesis process. By regulating the concentration of the copolymer and the temperature of the solution, the triblock copolymer Pluronic F-127 can induce the metal ions and organic ligands in the solution to assemble in a specific manner, thereby affecting the pore size distribution and pore morphology of the final product.
[0016] Acetic acid in a concentration range of 0.02M-0.1M is added to the triblock copolymer Pluronic F-127, the purpose of which is to provide a suitable chemical environment for the subsequent introduction of metal sources and the formation of metal organic frameworks by adjusting the pH value of the solution. Adding sodium chloride to the solution helps to adjust the ionic strength of the solution, further stabilize the metal ions in the solution, and improve the conductivity of the solution. The role of the sodium chloride is also to change the electrochemical properties of the solution, thereby helping to increase the rate and stability of the reaction. The concentration of added sodium chloride is between 0.1M and 1.0M.
[0017] After adding each component to the solution, it is necessary to fully mix them by stirring. The role of stirring is not only to make all the components fully dissolved and reacted, but also to adjust the temperature and molecular dynamics behavior of the solution by physical action. At a stirring rate of 300-400rpm, the triblock copolymer Pluronic F-127 molecules can self-assemble to form nano micelles or other ordered structures through hydrophobic interactions.
[0018] As a further embodiment of the present invention, in step S3, the organic ligand is a molecule or ion that forms a coordination complex with a metal ion, and is composed of terephthalic acid. Larger organic ligand molecules promote the formation of larger pores in the framework because they require more space to coordinate with metal ions. When terephthalic acid (BDC) is used as a ligand, in the synthesis of MOF, when the concentration range of terephthalic acid is 0.1M-0.5M, the pore size of the MOF is between 1.0nm-2.0nm; when the range of terephthalic acid is 0.5M-1.0M, the pore size of the MOF is between 2.0nm-3.5nm; when the range of terephthalic acid is 1.0M-2.0M, the pore size of the MOF is between 3.5nm-5.0nm.
[0019] N,N-dimethylformamide (DMF) is used for the synthesis of MOF. The N,N-dimethylformamide (DMF) has strong polarity, can effectively dissolve metal sources and promote the coordination reaction between metal ions and ligands. The increase in temperature will accelerate the coordination reaction between metal ions and ligands, and promote the formation of MOFs with larger pore sizes. Higher reaction temperatures can increase the reaction rate between metal ions and ligands, making the reaction process faster, thereby affecting the growth rate of the framework and the distribution of pore sizes. Under the synthetic conditions where the reaction temperature is between 150°C and 180°C, the pore size of the MOF material increases and the pore structure becomes more uniform. In addition, the increase in temperature can also improve the solubility of metal ions, thereby promoting the formation of MOFs with higher crystallinity, ultimately affecting their specific surface area and pore volume.
[0020] As a further embodiment of the present invention, in step S4, during the surface functionalization of the MOF material, specific functional groups are introduced, including amino and carboxyl groups, to enhance the hydrophilicity and electrochemiluminescence performance of the MOF material. The amino group can be introduced by using an amine compound (such as ethylenediamine) or by chemical vapor deposition technology, and the carboxyl group is introduced by a coordination reaction between a carboxylic acid compound and an unsaturated metal site in the framework.
[0021] The uncoordinated metal center or open coordination site in the MOF material is usually the main active site of the functionalization reaction. Through ligand exchange or chemical bonding, functional groups are introduced to the MOF surface to form stable chemical bonds. Surface functionalization can improve the electrochemical activity and stability of MOF. On the one hand, the introduction of amino groups can improve the hydrophilicity of the material, thereby enhancing its stability and adsorption capacity in the liquid phase. On the other hand, the carboxyl group can improve the electrochemiluminescence performance and catalytic activity of MOF by adjusting the electron density distribution.
[0022] After functionalization, the introduction and distribution of functional groups are verified by characterization methods, including Fourier transform infrared spectroscopy (FTIR) to detect the chemical characteristics of functional groups, X-ray photoelectron spectroscopy (XPS) to analyze the surface chemical composition, and scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to observe changes in surface morphology.
[0023] As a further embodiment of the present invention, in step S5, the synthesized MOF material contains impurities and unreacted reagents (such as solvents, metal ions or organic ligands), which need to be removed by washing and filtering. During the washing process, the selection of the washing solvent depends on the type of solvent used in the synthesis and the solubility characteristics of the reaction residues. Commonly used washing solvents include ethanol, dimethylformamide (DMF) and water.
[0024] During the washing process, controlling the amount and flow rate of the washing solvent can effectively avoid impurities remaining due to insufficient washing or damage to the framework structure due to excessive washing. Filtration is a continuation of washing, and its purpose is to remove the separated solid materials from the solution and avoid mechanical damage. In this process, a Buchner funnel or vacuum filtration equipment can be used, and the appropriate filter medium can be selected according to the particle size of the MOF material to ensure the integrity of the MOF material.
[0025] Before vacuum drying, a pretreatment can be performed to remove free water or volatile solvents adsorbed on the surface, which can be done by drying at a low temperature of 40°C or standing under an inert gas atmosphere. The vacuum drying process is carried out in stages, first at a low temperature of 60°C for several hours to remove surface adsorbed water and low-boiling point solvents; then gradually increasing the temperature to 100–120°C to completely remove high-boiling point solvents and deeply embedded impurities. While vacuum drying, attention should also be paid to the removal efficiency of water molecules, because some MOFs have a high adsorption capacity for water, which may cause pore blockage or lattice distortion. For this purpose, a dynamic vacuum system can be used to improve the water removal efficiency by continuously evacuating the vacuum. To prevent the shrinkage of pore size or changes in surface chemical properties during the drying process, specific protective agents such as organic amines or aluminum hydride can also be introduced before drying to stabilize the framework structure.
[0026] After drying, it is crucial to verify the structural and performance stability of the material through characterization. X-ray diffraction (XRD) can be used to detect whether the MOF crystal structure is intact; specific surface area tests (such as the BET method) can be used to evaluate the retention of the pore structure; Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) can further confirm whether the organic solvent or water has been completely removed.
[0027] As a further solution of the present invention, an application of a porous MOF is to use a functional porous metal organic framework material to construct an electrochemiluminescent sensing platform, which specifically includes the following steps: Step Z1, immersing the glassy carbon electrode in an electrodeposition solution containing metal nanoparticles, and depositing a uniformly distributed metal nanoparticle layer on the electrode surface by cyclic voltammetry.
[0028] Step Z2, dissolving the functionalized porous MOF in an ethanol-water mixed solvent to prepare a uniform dispersion; taking 10 μL of the dispersion and dropping it onto the surface of the electrode modified with metal nanoparticles, and drying it at room temperature to form a uniform MOF film.
[0029] Step Z3, take a phosphate-modified deoxyribonucleic acid (DNA) probe solution with a concentration of 5 μM, add it dropwise to the MOF-modified electrode surface, and incubate it at 4°C for 10 hours; after the incubation is completed, wash the electrode surface three times with phosphate buffer (PBS) with a pH of 7.4 to remove unbound probe molecules.
[0030] In step Z4, a microRNA (miRNA) auxiliary solution with a concentration of 1.5 μM and a volume of 8 μL was added dropwise to the DNA-modified electrode surface and incubated at 37°C for 2 hours; then, it was washed three times with PBS.
[0031] In step Z5, target miRNA solutions (volume 8 μL) of different concentrations were added to the modified electrode surface and reacted at 37°C for 60 minutes; then, the solution was washed three times with PBS to remove unbound miRNA molecules.
[0032] Step Z6, take a mixture of ferrocene-labeled hairpin nucleic acids H1 and H2 with a concentration of 1 μM and a volume of 8 μL, add it dropwise to the surface of the modified electrode, and react at 37° C. for 1.5 hours; then, wash it three times with PBS.
[0033] As a preferred embodiment, the metal nanoparticles are gold (Au) or platinum (Pt).
[0034] The technical effects and advantages of the preparation method and application of a porous MOF of the present invention: The present invention creates a suitable environment for the synthesis of MOF by means of self-assembly of triblock copolymer Pluronic F-127, adjusting the concentration of acetic acid and sodium chloride, controlling the stirring rate, etc., which is conducive to the formation of a specific pore structure. Through the metal ion diffusion optimization model, the temperature and reaction time are adjusted to ensure the uniform distribution of metal ions. The problem of uneven distribution of metal ions in existing MOF materials is solved. Surface functionalization introduces amino and carboxyl groups, enhances the surface stability and electrochemiluminescence activity of MOF, overcomes the defect of poor surface structure stability of existing materials, and improves the reliability of materials in electrochemical reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The present invention is a flow chart of a method for preparing a porous MOF.
[0036] Figure 2 This is the microscopic surface structure diagram of MOF material.
[0037] Figure 3 This is a schematic diagram of the adsorption isotherm of the MOF material after the amino group is introduced into the present invention.
[0038] Figure 4 This is a flow chart of the application of a porous MOF according to the present invention.
[0039] Figure 5 It is a curve diagram showing the relationship between the BDC ligand concentration and the MOF pore size of the present invention. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1 See also Figure 1 As shown in the flowchart, the embodiment of the present invention provides a method for preparing a porous MOF, which comprises the following steps: Step S1, dissolving the triblock copolymer Pluronic F-127 in ultrapure water, adding acetic acid and sodium chloride, and stirring to form a solution; Step S2, adding zirconium oxynitrate to the solution, and adjusting the temperature and reaction time to ensure uniform distribution of metal ions through a metal ion diffusion optimization model; Step S3, introducing organic ligands to adjust the pore size distribution of MOF; Step S4, performing surface functionalization on the synthesized MOF material to introduce amino groups and carboxyl groups; Step S5, washing and filtering the synthesized MOF material to remove impurities and residues, and then drying the MOF material under vacuum conditions to remove moisture and organic solvents.
[0042] Further, in the step S1, the triblock copolymer Pluronic F-127 is a block copolymer composed of polyether and polypropylene glycol (PPO), and its molecular structure characteristics enable it to spontaneously form a micellar structure in the solution. The molecular self-assembly behavior of the triblock copolymer Pluronic F-127 in the solution helps to form a microstructure, which can not only adjust the viscosity and interfacial tension of the solution, but also affect the formation of the MOF pore structure during the synthesis process. By regulating the concentration of the copolymer and the temperature of the solution, the triblock copolymer Pluronic F-127 can induce the metal ions and organic ligands in the solution to assemble in a specific manner, thereby affecting the pore size distribution and pore morphology of the final product. Acetic acid with a concentration range of 0.02M-0.1M is added to the triblock copolymer Pluronic F-127, the purpose of which is to provide a suitable chemical environment for the subsequent introduction of metal sources and the formation of metal organic frameworks by adjusting the pH value of the solution. Adding sodium chloride to the solution helps to adjust the ionic strength of the solution, further stabilize the metal ions in the solution, and improve the conductivity of the solution. The role of the sodium chloride is also to change the electrochemical properties of the solution, thereby helping to improve the rate and stability of the reaction. The concentration of sodium chloride added is between 0.1M-1.0M. After the components are added to the solution, they need to be fully mixed by stirring. The role of stirring is not only to make all the components fully dissolved and reacted, but also to regulate the temperature and molecular dynamics behavior of the solution through physical effects. At a stirring rate of 300-400rpm, the triblock copolymer Pluronic F-127 molecules can self-assemble to form nanomicelles or other ordered structures through hydrophobic interactions.
[0043] Furthermore, in step S2, the steps of the metal ion diffusion optimization model are as follows: Step Q1, the metal ion diffusion equation after adding zirconium oxynitrate into the solution is: ,in, is the concentration of metal ions in zirconium oxynitrate, is the diffusion coefficient, is the Laplace operator; Step Q2, use the Arrhenius equation to describe the effect of temperature on the diffusion coefficient Impact: ,in, is the pre-exponential factor, is the activation energy, is the gas constant, is temperature; Step Q3, the solution concentration distribution during the reaction follows: ,in, is the initial metal ion concentration, is the spatial position of the metal ion in the solution, is the reaction time, is the error function; Step Q4, establish the objective function, combine temperature and time, and optimize the uniformity of metal ions: ,in, is the length of the solution container, is the average concentration of metal ions, by adjusting the temperature and reaction time , to achieve uniform distribution of metal ions.
[0044] In the metal ion diffusion optimization model, satisfy , in order to make the concentration of metal ions uniformly distributed, minimize the objective function , the calculation formula is: , locally linearize the error function and calculate the gradient of the objective function: , , iteratively update the temperature by gradient descent method and reaction time , the update formula is as follows: , ,in, is the learning rate, which controls the step size of each update.
[0045] In this embodiment, the present invention verifies the influence of temperature and reaction time on the distribution of metal ion concentration in the metal ion diffusion optimization model by different temperature, time conditions and metal ion concentration. Experimental parameters: the metal source is zirconium nitrate; the solution concentration is 0.1M, 0.5M, 1.0M; the temperature conditions are 25°C, 50°C, 75°C; the reaction time is 1 hour, 3 hours, 6 hours; the relationship between the diffusion coefficient and the temperature on the diffusion coefficient is given according to the Arrhenius equation. The experimental data are shown in the following table: Table 1 Distribution of metal ion concentrations under different temperature and time conditions
[0046] From Table 1, we can see that as the reaction time increases, the metal ion concentration gradually decreases, indicating that the metal ions diffuse in the solution and gradually become evenly distributed. For the low concentration (0.1M) experiment, the concentration of metal ions decreases faster; while for the high concentration (1.0M), the concentration decreases more slowly, indicating that the time required for the diffusion of metal ions is inversely proportional to the initial concentration. As the temperature increases, the diffusion coefficient (D) shows an upward trend, because the increase in temperature can increase the energy of molecular motion in the solution, thereby accelerating the diffusion of metal ions. The rate of concentration change increases with the extension of the reaction time. Under the same time conditions, the higher the temperature, the greater the rate of concentration change. Under 50°C and 75°C conditions, the diffusion coefficient increased by about 20% to 40% compared with that under 25°C conditions.
[0047] Further, in step S3, the organic ligand is a molecule or ion that forms a coordination complex with a metal ion, and is composed of terephthalic acid. Larger organic ligand molecules promote the formation of larger pores in the framework because they require more space to coordinate with metal ions. When terephthalic acid (BDC) is used as a ligand, the pore size in the MOF will be relatively large, which is suitable for applications such as gas storage. When terephthalic acid (BDC) is used as a ligand, in the synthesis of MOF, when the concentration range of terephthalic acid is 0.1M-0.5M, the pore size of the MOF is between 1.0nm-2.0nm; when the range of terephthalic acid is 0.5M-1.0M, the pore size of the MOF is between 2.0nm-3.5nm; when the range of terephthalic acid is 1.0M-2.0M, the pore size of the MOF is between 3.5nm-5.0nm. N,N-dimethylformamide (DMF) is used for the synthesis of MOF. The N,N-dimethylformamide (DMF) has strong polarity, can effectively dissolve metal sources and promote the coordination reaction between metal ions and ligands. The increase in temperature will accelerate the coordination reaction between metal ions and ligands, and promote the formation of MOFs with larger pore sizes. Higher reaction temperatures can increase the reaction rate between metal ions and ligands, making the reaction process faster, thereby affecting the growth rate of the framework and the distribution of pore sizes. Under the synthetic conditions where the reaction temperature is between 150°C and 180°C, the pore size of the MOF material increases and the pore structure becomes more uniform. In addition, the increase in temperature can also improve the solubility of metal ions, thereby promoting the formation of MOFs with higher crystallinity, ultimately affecting their specific surface area and pore volume.
[0048] Further, in step S4, refer to Figure 2 As shown in the structural diagram, during the surface functionalization process of MOF materials, specific functional groups, including amino and carboxyl groups, are introduced to enhance the hydrophilicity and electrochemiluminescence properties of MOF materials. The introduction of amino groups can be carried out by using amine compounds (such as ethylenediamine) or by chemical vapor deposition technology, and the introduction of carboxyl groups is achieved by coordination reaction between carboxylic acid compounds and unsaturated metal sites in the framework. The uncoordinated metal centers or open coordination sites in the MOF materials are usually the main active sites for functionalization reactions. Functional groups are introduced to the MOF surface through ligand exchange or chemical bonding to form stable chemical bonds. Surface functionalization can enhance the electrochemical activity and stability of MOF. On the one hand, the introduction of amino groups can increase the hydrophilicity of the material, thereby enhancing its stability and adsorption properties in the liquid phase. As Figure 3 The adsorption isotherms shown show that the introduction of amino groups enhances the adsorption performance of MOF.
[0049] On the other hand, carboxyl groups can improve the electrochemiluminescence performance and catalytic activity of MOF by adjusting the electron density distribution. After the functionalization is completed, the introduction and distribution of functional groups are verified by characterization methods. The characterization methods include Fourier transform infrared spectroscopy (FTIR) to detect the chemical characteristics of functional groups, X-ray photoelectron spectroscopy (XPS) to analyze the surface chemical composition, and scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to observe changes in surface morphology.
[0050] Further, in the step S5, the synthesized MOF material contains impurities and unreacted reagents (such as solvents, metal ions or organic ligands), which need to be removed by washing and filtering processes. During the washing process, the selection of the washing solvent depends on the type of solvent used in the synthesis and the solubility characteristics of the reaction residues. Commonly used washing solvents include ethanol, dimethylformamide (DMF) and water. During the washing process, controlling the amount and flow rate of the washing solvent can effectively avoid impurity residues due to insufficient washing or damage to the framework structure due to excessive washing. Filtration is a continuation of washing, and its purpose is to remove the separated solid material from the solution and avoid mechanical damage. In this process, a Buchner funnel or a vacuum filtration device can be used, and an appropriate filter medium can be selected according to the particle size of the MOF material to ensure the integrity of the MOF material. Before vacuum drying, pretreatment can be performed to remove free water or volatile solvents adsorbed on the surface, and the pretreatment is completed by drying at a low temperature of 40°C or standing in an inert gas atmosphere. The vacuum drying process is carried out in stages, starting with a low temperature of 60°C for several hours to remove surface adsorbed water and low-boiling point solvents; then gradually increasing the temperature to 100–120°C to completely remove high-boiling point solvents and deeply embedded impurities. During vacuum drying, attention should also be paid to the removal efficiency of water molecules, because some MOFs have a high adsorption capacity for water, which may cause pore blockage or lattice distortion. To this end, a dynamic vacuum system can be used to improve the water removal efficiency by continuously evacuating the vacuum. To prevent the shrinkage of pore size or changes in surface chemical properties during the drying process, specific protective agents such as organic amines or aluminum hydride can also be introduced before drying to stabilize the framework structure. After drying, it is crucial to verify the structural and performance stability of the material through characterization methods. X-ray diffraction (XRD) can be used to detect whether the MOF crystal structure is intact; specific surface area tests (such as the BET method) can be used to evaluate the retention of pore structure; Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) can further confirm whether the organic solvent or water has been completely removed.
[0051] Example 2
[0052] See also Figure 4 As shown in the flowchart, an embodiment of the present invention provides an application of a porous MOF, which includes the following steps: Step Z1, immersing the glassy carbon electrode in an electrodeposition solution containing metal nanoparticles, and depositing a uniformly distributed metal nanoparticle layer on the electrode surface by cyclic voltammetry.
[0053] Step Z2, dissolving the functionalized porous MOF in an ethanol-water mixed solvent to prepare a uniform dispersion; taking 10 μL of the dispersion and dropping it onto the surface of the electrode modified with metal nanoparticles, and drying it at room temperature to form a uniform MOF film.
[0054] Step Z3, take a phosphate-modified deoxyribonucleic acid (DNA) probe solution with a concentration of 5 μM, add it dropwise to the MOF-modified electrode surface, and incubate it at 4°C for 10 hours; after the incubation is completed, wash the electrode surface three times with phosphate buffer (PBS) with a pH of 7.4 to remove unbound probe molecules.
[0055] In step Z4, a microRNA (miRNA) auxiliary solution with a concentration of 1.5 μM and a volume of 8 μL was added dropwise to the DNA-modified electrode surface and incubated at 37°C for 2 hours; then, it was washed three times with PBS.
[0056] In step Z5, target miRNA solutions (volume 8 μL) of different concentrations were added to the modified electrode surface and reacted at 37°C for 60 minutes; then, the solution was washed three times with PBS to remove unbound miRNA molecules.
[0057] Step Z6, take a mixture of ferrocene-labeled hairpin nucleic acids H1 and H2 with a concentration of 1 μM and a volume of 8 μL, add it dropwise to the surface of the modified electrode, and react at 37° C. for 1.5 hours; then, wash it three times with PBS.
[0058] Example 3
[0059] In the preparation process of MOF based on terephthalic acid (BDC) ligand to regulate pore size distribution, the pore size and structure of MOF can be controlled by adjusting the reaction conditions and ligand concentration. 0.2M BDC was dissolved in the polar solvent N,N-dimethylformamide (DMF). As a solvent, DMF has strong solubility, can effectively dissolve organic ligands and metal precursors, and promote the coordination reaction between metal and ligand. Subsequently, 0.1 M zirconium oxynitrate was added as a metal ion source to participate in the framework assembly process together with organic ligands. To ensure a suitable reaction environment, the pH value of the solution needs to be adjusted to 3 by adding concentrated nitric acid. This acidic environment can improve the solubility of metal ions and promote efficient coordination between metal and ligand. After the modulation is completed, the reaction solution is transferred to a closed high-pressure reactor and reacted at a high temperature of 180°C for 24 hours. High temperature conditions can significantly improve the reactivity of metal ions and ligands and promote the nucleation and growth of the MOF framework. In this process, by changing the initial concentration of BDC, the pore size of the final MOF material can be effectively controlled. Figure 5 As shown in the graph, when the BDC concentration is 0.1 M, the pore size of the synthesized MOF is about 1.5 nm; and when the BDC concentration increases to 0.5 M, the pore size increases to 3.5 nm.
[0060] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
[0061] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous MOF, characterized in that: The steps include: Step S1, dissolving the triblock copolymer Pluronic F-127 in ultrapure water, adding acetic acid and sodium chloride, and stirring to form a solution; Step S2, adding zirconium oxynitrate to the solution, and adjusting the temperature and reaction time to ensure uniform distribution of metal ions through a metal ion diffusion optimization model; Step S3, introducing organic ligands to adjust the pore size distribution of MOF; Step S4, performing surface functionalization on the synthesized MOF material to introduce amino groups and carboxyl groups; Step S5, washing and filtering the synthesized MOF material to remove impurities and residues, and then drying the MOF material under vacuum conditions to remove moisture and organic solvents; The steps of the metal ion diffusion optimization model are as follows: Step Q1, the metal ion diffusion equation after adding zirconium oxynitrate into the solution is: ,in, is the concentration of metal ions in zirconium oxynitrate, is the diffusion coefficient, is the Laplace operator; Step Q2, use the Arrhenius equation to describe the effect of temperature on the diffusion coefficient Impact: ,in, is the pre-exponential factor, is the activation energy, is the gas constant, is temperature; Step Q3, the solution concentration distribution during the reaction follows: ,in, is the initial metal ion concentration, is the spatial position of the metal ion in the solution, is the reaction time, is the error function; Step Q4, establish the objective function, combine temperature and time, and optimize the uniformity of metal ions: ,in, is the length of the solution container, is the average concentration of metal ions, by adjusting the temperature and reaction time , to achieve uniform distribution of metal ions.
2. The method for preparing a porous MOF according to claim 1, characterized in that ,In the metal ion diffusion optimization model, satisfy , in order to make the concentration of metal ions uniformly distributed, minimize the objective function , the calculation formula is: , locally linearize the error function and calculate the gradient of the objective function: , , iteratively update the temperature by gradient descent method and reaction time , the update formula is as follows: , ,in, is the learning rate, which controls the step size of each update.
3. The method for preparing a porous MOF according to claim 1, characterized in that In the step S1, acetic acid with a concentration range of 0.02M-0.1M is added to the triblock copolymer Pluronic F-127 solution, the pH value of the solution is adjusted, and sodium chloride with a concentration of 0.1M-1.0M is added; the stirring rate is 300-400rpm.
4. The method for preparing a porous MOF according to claim 1, characterized in that: In the step S3, the organic ligand is composed of terephthalic acid. When the concentration of terephthalic acid is 0.1M-0.5M, the pore size of MOF is between 1.0nm-2.0nm; when the concentration is 0.5M-1.0M, the pore size of MOF is between 2.0nm-3.5nm; when the concentration is 1.0M-2.0M, the pore size of MOF is between 3.5nm-5.0nm; using N,N-dimethylformamide as a solvent, at a reaction temperature of 150°C to 180°C, the pore size of the MOF material increases.
5. The method for preparing a porous MOF according to claim 1, characterized in that: In step S4, amino groups are introduced by using amine compounds or chemical vapor deposition technology, and carboxyl groups are introduced by the coordination reaction of carboxylic acid compounds with unsaturated metal sites in the framework.
6. The method for preparing a porous MOF according to claim 5, characterized in that: After functionalization, the introduction and distribution of functional groups were verified by Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, and transmission electron microscopy.
7. The method for preparing a porous MOF according to claim 1, characterized in that: In step S5, pretreatment is performed by low-temperature drying at 40°C or standing in an inert gas atmosphere before vacuum drying. The vacuum drying is first performed at 60°C for several hours and then heated to 100-120°C. A dynamic vacuum system is used to improve the efficiency of water removal. Before drying, an organic amine or aluminum hydride protective reagent is introduced to stabilize the framework structure.
8. The method for preparing a porous MOF according to claim 6, characterized in that: After drying, the structural and performance stability of the material were verified by X-ray diffraction, specific surface area test, Fourier transform infrared spectroscopy and thermogravimetric analysis.
9. An application of a porous MOF, characterized in that: The electrochemiluminescence sensing platform is constructed using functional porous metal organic framework materials, including the following steps: Step Z1, immersing the glassy carbon electrode in an electrodeposition solution containing metal nanoparticles, and depositing a uniformly distributed metal nanoparticle layer on the electrode surface by cyclic voltammetry; Step Z2, dissolving the functionalized porous MOF in an ethanol-water mixed solvent to prepare a uniform dispersion; taking 10 μL of the dispersion and dropping it onto the surface of the electrode modified with metal nanoparticles, and drying it at room temperature to form a uniform MOF film; Step Z3, taking a phosphate-modified deoxyribonucleic acid probe solution with a concentration of 5 μM, adding it dropwise to the MOF-modified electrode surface, and incubating it at 4° C. for 10 hours; after the incubation is completed, washing the electrode surface three times with a phosphate buffer with a pH of 7.4 to remove unbound probe molecules; Step Z4, adding a microRNA auxiliary solution with a concentration of 1.5 μM and a volume of 8 μL to the surface of the DNA-modified electrode and incubating at 37° C. for 2 hours; then, washing with PBS three times; Step Z5, adding target miRNA solutions of different concentrations to the surface of the modified electrode and reacting at 37°C for 60 minutes; then, washing three times with PBS to remove unbound miRNA molecules; Step Z6, take a mixture of ferrocene-labeled hairpin nucleic acids H1 and H2 with a concentration of 1 μM and a volume of 8 μL, add it dropwise to the surface of the modified electrode, and react at 37° C. for 1.5 hours; then, wash it three times with PBS.
Citation Information
Patent Citations
Shaped MOF-based composite phase change material and preparation method and application thereof
CN110484213A
Preparation method and application of electrochemical luminescence activity fluorescence grading porous MOF (Metal Organic Framework)
CN118185051A
Heavy metal adsorbent using activated carbon loaded with zirconium-organic frameworks and manufacturing method thereof
KR101788527B1
Cited By
Functionalized MOF composite material, preparation method thereof and application of functional MOF composite material in glabridin purification
CN120424361A
Sensing material for detecting atmospheric carboxylic acid, preparation method, detection method and application
CN120923829A
Gd MOF composite material, immunosensor and preparation method and application thereof
CN121319392A